Meningkatnya Repeat Purchasedengan Content Marketing dan Brand Performance Melalui Customer Engagement Pada Konsumen Produk Fashion Merek Uniqlo - Dyah Ika Kirana Jalantina; Maria Magdalena Minarsih (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2021)
This study aims to analyze and examine the effect of content marketing and brand performance on repeat purchases with customer engagement as an intervening variable on consumers of Uniqlo brand clothing products. With content marketing that is interesting, relevant and understands the target market, as well as a strong brand performance in occupying a brand position in the market, it will create an attachment for consumers in terms of brand awareness so that consumers will make repeat purchases. The method used is multiple regression analysis. Data were collected using a questionnaire. The sample in this study was taken as many as 100 respondents with an age of more than or equal to 17 years who had purchased Uniqlo brand fashion products. The results of this study indicate that content marketing has a positive and significant effect on customer engagement, brand performance has a positive and significant effect on customer engagement, content marketing has a positive and significant effect on repeat purchases, brand performance has a positive and significant effect on repeat purchases, customer engagement has a positive and significant impact on repeat purchases. significant to repeat purchases